Clinical and mutation analysis of 51 probands with anophthalmia and/or severe microphthalmia from a single center. Issue 1 (27th March 2013) - Gerth‐Kahlert, Christina; Williamson, Kathleen; Ansari, Morad; Rainger, Jacqueline K.; Hingst, Volker; Zimmermann, Theodor; Tech, Stefani; Guthoff, Rudolf F.; van, Veronica; FitzPatrick, David R.
Abstract Clinical evaluation and mutation analysis was performed in 51 consecutive probands with severe eye malformations – anophthalmia and/or severe microphthalmia – seen in a single specialist ophthalmology center. The mutation analysis consisted of bidirectional sequencing of the coding regions of SOX2, OTX2, PAX6 (paired domain), STRA6, BMP4, SMOC1, FOXE3, and RAX, and genome‐wide array‐based copy number assessment. Fifteen (29.4%) of the 51 probands had likely causative mutations affecting SOX2 (9/51), OTX2 (5/51), and STRA6 (1/51). Of the cases with bilateral anophthalmia, 9/12 (75%) were found to be mutation positive. Three of these mutations were large genomic deletions encompassing SOX2 (one case) or OTX2 (two cases). Familial inheritance of three intragenic, plausibly pathogenic, and heterozygous mutations was observed. An unaffected carrier parent of an affected child with an identified OTX2 mutation confirmed the previously reported nonpenetrance for this disorder. Two families with SOX2 mutations demonstrated a parent and child both with significant but highly variable eye malformations. Heterozygous loss‐of‐function mutations in SOX2 and OTX2 are the most common genetic pathology associated with severe eye malformations and bi‐allelic loss‐of‐function in STRA6 is confirmed as an emerging cause of nonsyndromal eye malformations.